2020
DOI: 10.1159/000511871
|View full text |Cite
|
Sign up to set email alerts
|

Modulating TSH Receptor Signaling for Therapeutic Benefit

Abstract: Autoimmune thyroid-stimulating antibodies are activating the thyrotropin receptor (TSHR) in both the thyroid and the eye, but different molecular mechanisms are induced in both organs, leading to Graves’ disease (GD) and Graves’ orbitopathy (GO), respectively. Therapy with anti-thyroid drugs to reduce hyperthyroidism (GD) by suppressing the biosynthesis of thyroid hormones has only an indirect effect on GO, since it does not causally address pathogenic TSHR activation itself. GO is thus very difficult to treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 81 publications
0
16
0
3
Order By: Relevance
“…The fact that they may not be widely available or affordable, as well as the lack of information, say, on the need of subsequent rehabilitative surgery, further add to their current limitations. As multiple pathogenic pathways are implicated in GO, several targeted therapies are worth exploring in clinical trials, e.g., monoclonal antibodies and/or small molecules targeting the TSHR (187,188) or the CD40 molecule expressed in both thyrocytes and orbital fibroblasts (189), or anti-IL-23/anti-IL-17 for the IL-23/IL-17 axis and sirolimus for the mTOR pathway (190). Worthwhile is also a modulating impact on the microbiome in patients with GO (191).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that they may not be widely available or affordable, as well as the lack of information, say, on the need of subsequent rehabilitative surgery, further add to their current limitations. As multiple pathogenic pathways are implicated in GO, several targeted therapies are worth exploring in clinical trials, e.g., monoclonal antibodies and/or small molecules targeting the TSHR (187,188) or the CD40 molecule expressed in both thyrocytes and orbital fibroblasts (189), or anti-IL-23/anti-IL-17 for the IL-23/IL-17 axis and sirolimus for the mTOR pathway (190). Worthwhile is also a modulating impact on the microbiome in patients with GO (191).…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 36 The exact mechanism in the progression of TAO is unclear although several studies implicate TSHR and IGF-1R, which are both upregulated in the OFs of patients with TAO. 5 , 37 The miRNA regulation of genes involved in TAO is gaining interest, 38 therefore, in our study, we focused on miRNA that may be involved in the regulation of the inflammasome in TAO using relevant markers such as NLRP3. We found a number of miRNAs that were differentially regulated in the orbital connective tissue of TAO patients and confirmed that three of these were significantly upregulated (miR-22, miR-27b, and miR-378) and one was significantly downregulated (miR-143).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have arrived at similar conclusions, the two receptors share interacting signal pathways but may not necessarily activate each other. 5 , 9 However, immunoprecipitation results in some studies have suggested that TSHR and IGF-1R may colocalize. 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An approach to stimulate the TSH receptor may be the use of allosteric regulators with the activity of full agonists [ 5 , 6 ]. Their characteristic feature is the ability to stimulate receptors of pituitary glycoprotein hormones that contain inactivating mutations in the ectodomain and are, therefore, insensitive to hormones [ 5 ].…”
mentioning
confidence: 99%